Écriture Féminine in Ken Bugul’s De L’Autre Côté du Regard - Subekti, Mega; Maulana, Sandya; Sarathan, Indra (Universitas Mulawarman, 2025)
The article analyzes the representation of écriture féminine in Ken Bugul's De L’Autre Côté du Regard (DLCR) and its connection to feminist ideology and the narrator’s hybrid cultural identity. This research applies a close reading technique, utilizing the framework of feminist narratology by Lanser (1986) and écriture féminine by Cixous (1976) and Brahimi (2000). Through data analysis, it is found that the narrative structure of DLCR, which represents the concept of écriture féminine, appears very fluid and non-linear, similar to writing pattern of memoirs. Repetitive phrases are found that represent the narrator’s deepest emotions regarding her maternal relationship and her in-between identity within postcolonial context. The results indicate that the structure of écriture féminine in DLCR appears to represent the narrator’s process of reconciliation, not only related to the maternal relationship with her biological mother but also to her motherland, Senegal. By incorporating the voice of other women, the text opens up a collective space of solidarity emblematic of African feminism. DLCR's narrative is argued to offer a distinctly African reinterpretation of feminism where bodily experience, ancestral tradition, and political resistance converge, ultimately presenting writing as an aesthetic and emancipatory act of postcolonial female self-definition.